2019
DOI: 10.3390/cancers11010096
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Vaccine Encoding SA-4-1BBL Fused to HPV-16 E7 Antigen Has Prophylactic and Therapeutic Efficacy in a Cervical Cancer Mouse Model

Abstract: The SA-4-1BBL, an oligomeric novel form of the natural ligand for the 4-1BB co-stimulatory receptor of the tumor necrosis factor (TNF) superfamily, as a recombinant protein has potent pleiotropic effects on cells of innate, adaptive, and regulatory immunity with demonstrated therapeutic efficacy in several tumor models. However, the production of soluble form of SA-4-1BBL protein and quality control is time and resource intensive and face various issues pertinent to clinical development of biologics. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Another DNA vaccine (SP-SA-E7-1BBL) encoding SA-4-1BBL fused to HPV16 E7 antigen has shown promising results in preclinical studies. 122 SA-4-1BBL is an oligomeric form of the ligand 4-1BB receptor of the TNF superfamily, which has been shown to have proinflammatory effects when it is engaged. The fusion of SA-4-1BBL to HPV16 E7, administered via gene gun, showed increased anti-tumor efficacy in the TC-1 model compared to controls, and also increased IFNγ-producing E7-specific T cells.…”
Section: Hpv Dna-based Vaccinesmentioning
confidence: 99%
“…Another DNA vaccine (SP-SA-E7-1BBL) encoding SA-4-1BBL fused to HPV16 E7 antigen has shown promising results in preclinical studies. 122 SA-4-1BBL is an oligomeric form of the ligand 4-1BB receptor of the TNF superfamily, which has been shown to have proinflammatory effects when it is engaged. The fusion of SA-4-1BBL to HPV16 E7, administered via gene gun, showed increased anti-tumor efficacy in the TC-1 model compared to controls, and also increased IFNγ-producing E7-specific T cells.…”
Section: Hpv Dna-based Vaccinesmentioning
confidence: 99%
“…This vaccine induced higher prophylactic and therapeutic effects in TC-1 tumor model in vivo compared to mice treated with SP-SA-4-1BLL or E7 only, in relation to an increase in E7-specific T cells producing IFN-γ. Furthermore, this vaccine established long-term immunologic memory that prevents recurrence [115]. The use of co-stimulatory molecules of the TNF superfamily seems to enhance the immune response achieved with vaccines.…”
Section: Genetic Immunopotentiation Therapiesmentioning
confidence: 99%
“…Another field of future research is chimeric antigen receptor (CAR)-T cells, genetically modified T cells that could be used to target the specific E6 and E7 oncoproteins. They have been developed against a wide variety of tumor antigens, mainly hematologic malignancies [114,115].…”
Section: Future Directionsmentioning
confidence: 99%
“…Several reports have demonstrated that specific antitumor immune responses can be elicited using naked DNA vaccines encoding 4-1BBL in conjunction with TAAs [ 9 , 10 , 11 ]. These types of vaccines are cheap to produce, easy to construct, and have a long shelf life, plus they can be quickly manufactured for preclinical trials.…”
Section: Introductionmentioning
confidence: 99%